Antiglycation and antioxidant activities of the crude extract and saponin fraction of Tribulus terrestris before and after microcapsule release - Figueiredo, Célia Cristina Malaguti [UNESP]; da Costa Gomes, Amanda [UNESP]; Granero, Filipe Oliveira [UNESP]; Bronzel Junior, João Luiz [UNESP]; Silva, Luciana Pereira; Ximenes, Valdecir Farias [UNESP]; da Silva, Regildo Márcio Gonçalves [UNESP] (Elsevier, 2022)
Objective: The present study investigated antiglycation and antioxidant activities of crude dry extract and saponin fraction of Tribulus terrestris. It also developed a method of microencapsulation and evaluated antiglycation and antioxidant activities of crude dry extract and saponin fraction before and after microcapsule release. Methods: Antiglycation activity was determined by relative electrophoretic mobility (REM), free amino groups and inhibition of advanced glycation end-product (AGE) formation. Antioxidant activity was determined by 2,2-diphenyl-1-picrylhydrazyl (DPPH), ferric ion-reducing antioxidant power (FRAP), nitric oxide (NO) and thiobarbituric acid reactive species (TBARS) tests. Microcapsules were prepared using maltodextrin as wall material and freeze-drying as encapsulation technique. Morphological characterization of microcapsules was evaluated by scanning electron microscopy, and encapsulation efficiency and microcapsule release were determined by total saponins released. Antiglycation and antioxidant assays were performed using crude dry extract and saponin fraction of T. terrestris before and after release. Results: Saponin fraction showed an increase of 32.8% total saponins. High-performance liquid chromatography-mass spectrometry analysis showed the presence of saponins in the obtained fraction. Antiglycation evaluation by REM demonstrated that samples before and after release presented antiglycation activity similar to bovine serum albumin treated with aminoguanidine. Additionally, samples inhibited AGE formation, highlighting treatment with saponin fraction after release (89.89%). Antioxidant tests demonstrated antioxidant activity of the samples. Crude dry extract before encapsulation presented the highest activities in DPPH (92.00%) and TBARS (32.49%) assays. Saponin fraction before encapsulation in FRAP test (499 μmol Trolox equivalent per gram of dry sample) and NO test (15.13 μmol nitrite formed per gram of extract) presented the highest activities. Conclusion: This study presented antiglycation activity of crude dry extract and saponin fraction of T. terrestris, besides it demonstrated promising antioxidant properties. It also showed that the encapsulation method was efficient and maintained biological activity of bioactive compounds after microcapsule release. These results provide information for further studies on antidiabetic and antiaging potential, and data for new herbal medicine and food supplement formulations containing microcapsules with crude extract and/or saponin fraction of T. terrestris.
Keywords: Glycation; Microencapsulation; Oxidative stress; Saponins; Tribulus terrestris